Community policing: international patterns and comparative perspectives - Wisler, Dominique (Advances in police theory and practice series, 2009)
Rethinking police and society : community policing in comparison -- Community policing in a high crime transitional state : the case of South Africa since democratization in 1994 -- Reforming community, reclaiming the state : the development of sungusungu in Northern Tanzania -- Community policing : the case of informal policing in Nigeria -- The French centralized model of policing : to control the citizens -- Community policing in Belgium : the vicissitudes of the development of a police model -- Patterns of community policing in Britain -- Community policing in the United States : social control through image management -- Fit for purpose : working with the community to strengthen policing in Victoria, Australia -- A Chinese theory of community policing -- The police, community, and community justice institutions in India -- Community policing and police reform in Latin America